2018
DOI: 10.3390/nu10091196
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Biological Activities of Essential Oils of Curcuma Species

Abstract: Members of the genus Curcuma L. have been used in traditional medicine for centuries for treating gastrointestinal disorders, pain, inflammatory conditions, wounds, and for cancer prevention and antiaging, among others. Many of the biological activities of Curcuma species can be attributed to nonvolatile curcuminoids, but these plants also produce volatile chemicals. Essential oils, in general, have shown numerous beneficial effects for health maintenance and treatment of diseases. Essential oils from Curcuma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
183
2
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 300 publications
(254 citation statements)
references
References 246 publications
5
183
2
11
Order By: Relevance
“…Zingiberaceae; chloroplast genome; phylogenetic analysis; single nucleotide polymorphism Curcuma zedoaria, commonly known as 'zedoary' and 'white turmeric' in English and 'ezhu' in Chinese, is an important Curcuma with an ancient medicinal history in China and Japan, where the plant is used as a carminative and stomachic (Branney 2005;Dosoky and Setzer 2018). The essential oil of zedoary essential oil is used in the perfume and liquor industries, and the bitter-tasting rhizome is used in the preparation of some curry powders and eaten as a vegetable in Thailand (Branney 2005).…”
Section: Curcuma Zedoaria;mentioning
confidence: 99%
“…Zingiberaceae; chloroplast genome; phylogenetic analysis; single nucleotide polymorphism Curcuma zedoaria, commonly known as 'zedoary' and 'white turmeric' in English and 'ezhu' in Chinese, is an important Curcuma with an ancient medicinal history in China and Japan, where the plant is used as a carminative and stomachic (Branney 2005;Dosoky and Setzer 2018). The essential oil of zedoary essential oil is used in the perfume and liquor industries, and the bitter-tasting rhizome is used in the preparation of some curry powders and eaten as a vegetable in Thailand (Branney 2005).…”
Section: Curcuma Zedoaria;mentioning
confidence: 99%
“…On the basis of phytochemical studies on Curcuma oils, sesquiterpenoids, and monoterpenoids have been identified as the major active constituents. The essential oil of Curcuma species is reported to possess a wide range of pharmacological activities such as anti‐inflammatory, antiproliferative, hypocholesterolaemic, antidiabetic, diuretic, antirheumatic, hypotensive, antioxidant and cyclooxygenase‐1 (COX‐1) inhibitory activities (Dosoky et al, ). Curcuma zedoaria has been investigated for its effect on CYP3A4 enzymes in a Caco‐2 cell model treated with methanolic extract of rhizome for a period of 72 h. The extract considerably decreased the activity of CYP3A4 by 85–98% (IC 50 : 0.014 mg/ml) (Hou et al, ).…”
Section: Herbs Postulated To Induce Hdi With Cardiovascular Drugsmentioning
confidence: 99%
“…Zedoary turmeric oil is a volatile oil extracted from Rhizoma Sparganii (RC). As an effective anti-tumor drug (Chang et al, 2019), the main active ingredients of zedoary turmeric oil are curcumin, curcumin diketone and β-elemene (Dosoky and Setzer, 2018).…”
Section: Rhizoma Curcumae and Rhizoma Sparganii (Rcrs) Is Frequently mentioning
confidence: 99%